Освобождение: киноэпопея / авторы сценария: Ю. Бондарев, О. Курганов, Ю. Озеров - Бондарев Юрий Васильевич (Искусство, 1985)
Экземпляры: АБ (1985) / Инвентарный номер: 10550 / Авт.знак: Б 81 / ББК: 85.374(2)